An aspect-oriented approach for improving architecture design efficiency - Keuler, Thorsten (International Conference on Software Engineering 2008, 2008)
Major issues in software engineering today are the ever increasing size and complexity of systems with, at the same time, high demands for quality. Software architectures are a means for coping with size and complexity of systems and also for assuring required qualities. The processes of creating architectures, however, remain affected by these issues. Since, in practice, architectures have to be constructed iteratively, the number of established architectural strategies and the number of inter-related models heavily increase over time. Hence, the impact analysis of newly introduced quality strategies during later stages becomes highly effort-intensive and error-prone. With our approach we aim at the mitigation of effort needed for such quality impact analyses by enabling efficient separation of concerns. For achieving efficiency, we introduce an aspect-oriented approach that enables the automatic weaving of quality strategies into architectural artifacts. By doing so, we are able to conduct selective quality impact evaluations with significantly reduced effort.